EFFECTIVENESS OF INQUIRY BASED LEARNING METHOD TO INCREASE STUDENTS CRITICAL THINKING SPEAKING SKILL SMA PARULIAN 2 MEDAN - Agresia Meirani Telaumbanua (English Education Department at FKIP Nommensen University, 2019)
This research isintended to find out Effectiveness of Inquiry Based Learning Method to Increase Students Critical Thinking Speaking Skill SMA Parulian 2 Medan. This research is conducted by applying Quantitative Experimental research. The sample of this research is two classes that consist 60 students which were selected by using random sampling technique. The first group is class XI MIA 2 (consist of 30 students) as a experimental class and class XI IPS 1 (consist of 30 students) as a control group. The instrument used for collecting the data is by giving the students speaking test. The test consist of pre-test, and post-test. The data was analyzed by using t-test formula in order to see wheter Inquiry Based Learning Method affects Students’ Speaking skill or not. The result of the analysis showed that t-observed is 4,43 higher than t-table 1,671 at level significance 0,05 with the degree of freedom 58. It means that alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. Therefore there is significant affect of Inquiry Based Learning Method on Students’s Speaking Skill of Eleventh Grade at SMA Parulian 2 Medan. Therefore Inqury Based Learning Method can be applied by English Teacher in teaching speaking skill.